Study of Maximum Sustainable Yield of Rabbitfish (Siganus sp.) in Makassar Waters - Umar, Moh. Tauhid; Andy Omar, Sharifuddin Bin; Suwarni, Suwarni (Hasanuddin University, 2020)
This study aims to estimate the potential of fish resources which include catch per unit effort (CPUE), Maximum Sustainable Yield (MSY), optimum efforts, exploitation rates and total allowable catch (TAC) of Rabbitfish in Makassar waters. This study uses time-series data, namely annual data from the fisheries statistics report at the Office of Marine and Fisheries Service, South Sulawesi Province from 2007 until. 2016. The method used to predict fish resource potential in the study is the Surplus Production method referring to the Schaefer model. The results of the study showed that the average production and standard efforts in the 10-year period were 78.8 tons per year and 1304 standard units per year respectively. The estimation results obtained by MSY and the optimum efforts of rabbitfish per year were 104 tons and 1142 standard units, respectively and total allowable catches (TAC) are 82.979 tons per year. The level of utilization of rabbitfish resources in Makassar waters in the last three years has been overexploitation.